2020
DOI: 10.9734/jamps/2020/v22i1230208
|View full text |Cite
|
Sign up to set email alerts
|

L-Citrulline Supplementation Enhances Reproductive Functions of Lead Acetate Induced Testicular Toxicity in Male Sprague Dawley Rats

Abstract: Introduction: Lead (Pb) is a transition metal and a known male reproductive toxicant that induces its effects mainly through oxidative stress. This study investigated the effects of L-Citrulline (Cit) supplement on reproductive functions and antioxidant activities in Lead acetate treated male rats. Materials and Methods: Twenty  male rats (180-200 g) were grouped into four  and treated as follows; Group 1 (Control), given distilled water, Group 2 was given Pb acetate (2.25mg/kg), Group 3 was co-treated with Pb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
1
1
0
Order By: Relevance
“…Some researchers have reported histopathological findings demonstrating structural changes in testis due to heavy metal toxicity such as lead acetate. Consistent with previous studies, our present study revealed testicular injury, tubule atrophy, and spermatid retention in animals treated with lead acetate (Farombi et al, 2007; Kolawole et al, 2020). However, following therapy with cabbage juice, these histological alterations were significantly reduced.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Some researchers have reported histopathological findings demonstrating structural changes in testis due to heavy metal toxicity such as lead acetate. Consistent with previous studies, our present study revealed testicular injury, tubule atrophy, and spermatid retention in animals treated with lead acetate (Farombi et al, 2007; Kolawole et al, 2020). However, following therapy with cabbage juice, these histological alterations were significantly reduced.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, sperm function markers examined were affected negatively following exposure to lead acetate (Pb) (Figure 4a–c), which is consistent with earlier findings (Abdel‐Moniem et al, 2010; Elgawish & Abdelrazek, 2014; Sudjarwo & Sudjarwo, 2017). Lead has been shown to reduce sperm motility, viability and functional maturity in the past (Hernandez et al, 2005; Kolawole et al, 2020; Naha et al, 2005). Reports has linked decrease in sperm count and disruption of spermatogenesis in rats with lead exposure (Batra et al, 2001; Wadi & Ahmad, 1999).…”
Section: Discussionmentioning
confidence: 99%